Scaling in cognitive performance reflects multiplicative multifractal cascade dynamics - Stephen, Damian G.; Anastas, Jason R.; Dixon, James A. (Frontiers in Physiology, 2012)
Self-organized criticality purports to build multi-scaled structures, such as those supporting life, out of local interactions. Evidence of scaling in various domains of biology may be more generally understood to reflect multiplicative interactions weaving together many disparate scales. The self-similarity of power-law scaling entails homogeneity: fluctuations distribute themselves similarly across many spatial and temporal scales. However, this apparent homogeneity can be misleading, especially as it spans more scales. Reducing biological processes to one power-law relationship neglects rich cascade dynamics. We review recent research into multifractality in executive-function cognitive tasks and propose that scaling reflects not criticality but instead interactions across multiple scales and among fluctuations of multiple sizes.